Sociological Insights for the Didactics of Sociology - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2013)
The article aims to analyse the relationship between sociology and didactics of sociology. This relationship is analysed from different perspectives. Firstly didactics of sociology is analysed from the viewpoint of so-called didactics of social sciences and civic education. Secondly the article analyses the development of the interrelation between theory of education and sociology of education and searches the ideas for the conceptualization of didactics of sociology in this development. Three forms of the interrelation between theory of education and sociology of education are distinguished. Educational sociology emerged as normative and applied discipline that has assisted educational theory to articulate the educational aims and the means of their implementation. The sociology of education that emphasized the scientific and empirical rather than normative character was an alternative for the educational sociology and has revealed different aspects of education that were ignored by educational sociologists. The phenomena of the hidden curricula and its role in social and cultural reproduction were among them. The third form of interrelation is associated with the movement of public sociology. The proponents of public sociology put forward the questions of social function of sociology and the significance of sociological literacy for democratic society. The concept of public sociology stimulates the discussions about didactics of sociology. Thirdly the article searches the ideas for the interpretation of the relationship between sociology and didactics of sociology in the development of the liaisons between history and didactics of history. The concept of historical consciousness and understanding of historical culture solve the contradiction between academic history and didactics of history.